Role of novel therapeutic agents in modulating invadopodia formation in metastatic breast cancer - Siti Nor Aini Harun,; Nurul Akmaryanti Abdullah,; Noraina Muhamad Zakuan,; Hafizah Abdul Hamid,; Muhammad Zulfadli Mehat,; Nur Fariesha Md Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The ability to colonize distant organs which is lethal has made metastatic breast cancer become the top ten causes of mortality worldwide. Specialized actin-rich protrusions termed invadopodia were thought to be formed by highly invasive cells to degrade the extracellular matrix to drive cancer invasion and metastasis. Identification of compound(s) to hinder the formation ofinvadopodia is important to resist the metastasis of breast cancer as well as to yield antimetastasis targeted therapy. The current review aims to provide new insights on cancer invasion and candidate compound(s) capable to disrupt invadopodia formation and invadopodia-related proteins.